2019
DOI: 10.51495/jurnalakrab.v10i2.290
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor yang Mempengaruhi Kemampuan Literasi Digital

Abstract: Penelitian ini bertujuan untuk menganalisis kemampuan literasi digital yang dipengaruhi oleh beberapa faktor yaitu: 1) keaktifan penggunaan media online, 2) prestasi akademik, 3) peran orangtua atau keluarga terhadap 4) intensitas membaca dan 5) kemampuan literasi digital. Penelitian ini merupakan jenis penelitian kuantitatif dengan metode survey. Responden penelitian ini adalah mahasiswa fakultas Ekonomi IBM asmi dengan pengambilan sampel purposive sebanyak 120 orang. Teknik pengumpulan data menggunakan instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 9 publications
0
7
0
3
Order By: Relevance
“…In other research, Syah, et al shows that the students' KPS is 9,8 in the low category, Putri, et al found the precentage of student's KPS is 31.82 %, and Safahi, et al explained that the learning with practicum improves students science process skills seen from their learning outcomes [40][41][42]. However, the KPS of students in this research are considered quite high in both class X MIPA 3 and X MIPA 5.…”
Section: Resultsmentioning
confidence: 95%
“…In other research, Syah, et al shows that the students' KPS is 9,8 in the low category, Putri, et al found the precentage of student's KPS is 31.82 %, and Safahi, et al explained that the learning with practicum improves students science process skills seen from their learning outcomes [40][41][42]. However, the KPS of students in this research are considered quite high in both class X MIPA 3 and X MIPA 5.…”
Section: Resultsmentioning
confidence: 95%
“…Digital literacy is needed for the use of technology in communication within the IbuSibuk community. Digital literacy includes the understanding, skills, and abilities of individuals to use digital technology (Syah, Darmawan, & Purnawan, 2019). In the IbuSibuk Community, there are several members who still have difficulty using applications such as Zoom or Telegram.…”
Section: The Use Of Technology In Community Communicationmentioning
confidence: 99%
“…In this case, students often use digital media access due to facilities, economic status, and the role of parents in supporting students in accessing technology. It is under the opinion (Syah et al, 2019). In addition, the pandemic has caused the intensity of access to technology to increase (Gusty et al, 2020).…”
Section: Path Coefficientsmentioning
confidence: 99%